Lead bromide cesium-based perovskite nano photocatalyst, preparation method and application thereof

Through stress control, the lead cesium-based perovskite nanowire photocatalyst is solved, the photogenerated carrier recombination problem in semiconductor photocatalysts is improved, the CO2 reduction efficiency and catalytic performance is improved, the process is simplified and the cost is reduced, and the Efficient and controllable photocatalytic carbon dioxide reduction.

CN119140174AInactive Publication Date: 2024-12-17YANGTZE DELTA REGION INST OF UNIV OF ELECTRONICS SCI & TECH OF CHINE (HUZHOU)
View PDF 16 Cites 0 Cited by

Patent Information

Application Number
CN202411624123.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2024-12-17
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The recombination problem of photogenerated carriers in existing semiconductor photocatalysts leads to a decrease in the number of electron holes, limiting the efficiency of CO2 reduction reaction, and the performance of perovskite-based nanophotocatalysts does not meet expectations, making the preparation process complex and difficult to control.

Method used

The preparation method of lead bromide-based cesium perovskite nanowire photocatalyst with adjustable stress is used to form CsPbBr3-based perovskite nanowires with bending stress structure to improve photogenesis Carrier separation efficiency and catalytic performance.

Benefits of technology

It significantly improves the photogenerated carrier separation efficiency and photocatalytic performance, improves the CO2 reduction reaction rate and product selectivity, simplifies the preparation process and reduces production costs, and provides a more efficient and controllable photocatalytic carbon dioxide reduction technology.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119140174A_ABST
    Figure CN119140174A_ABST
Patent Text Reader

Abstract

The invention discloses a cesium lead bromide-based perovskite nano photocatalyst, a preparation method and application thereof, and the preparation method of the catalyst comprises the following steps: S1, adding a cesium source into octadecene, then adding oleic acid into the octadecene, then carrying out vacuum-pumping treatment and heating, and then raising the temperature until solids are completely dissolved to obtain a solution containing the cesium source; s2, a lead source is added into octadecene, then oleylamine and octylamine ligands are added into the octadecene, vacuumizing treatment is conducted, then the temperature is increased, and after heat preservation is conducted for a certain time, a solution containing the lead source is prepared; s3, controlling the adding amount of the solution containing the cesium source to react with the solution containing the lead source, and then controlling conditions to carry out quenching reaction; and S4, centrifuging the reacted solution, and subsequently centrifuging again by using a solvent to obtain the photocatalyst. The perovskite nanowire catalyst with the stress structure is applied to photocatalytic reduction of carbon dioxide, and the highest activity is 5 times that of unstressed perovskite nanowires.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of photocatalyst preparation, and in particular to a stress-adjustable one-dimensional cesium lead bromide (CsPbBr3)-based perovskite nanowire photocatalyst, a preparation method and application thereof in reducing carbon dioxide. Background Art

[0002] Photocatalysis is a green and sustainable technology. Taking the accumulation of greenhouse gases (such as CO2) in the atmosphere as an example, photocatalysis can effectively reduce CO2 to products with economic added value such as CO and CH4, achieving energy saving, pollution reduction, and carbon reduction. However, as the most important part of photocatalytic reduction of CO2 technology, the performance of semiconductor photocatalysts is still far from expectations. One important point is that the serious recombination of photogenerated carriers in semiconductor photocatalysts greatly reduces the number of electron holes involved in the catalytic reaction.

[0003] Perovskite nanocrystals have received great attention in related fields due to their unique optoelectronic properties. In recent years, there have also been some reports on their use in the field of photocatalytic CO2 reduction, indicating that perovskite nanocrystals have great potential in this field. Despite this, the performance of perovskite-based nanophotocatalysts is still far from expectations, and problems such as the recombination of photogenerated carriers remain one of the inevitable difficulties. In order to solve this problem, commonly used methods include doping, heterostructure construction, and co-catalyst loading. However, these methods often require complex preparation processes and problems such as difficulty in controlling the degree of interface matching. Summary of the invention

[0004] The present invention provides a one-dimensional CsPbBr3-based perovskite nanowire photocatalyst with adjustable stress, a preparation method and application thereof in reducing carbon dioxide, so as to solve the problems described in the background technology.

[0005] In order to solve the above technical problems, the present invention adopts the following technical solutions: A method for preparing a stress-adjustable lead bromide cesium-based perovskite nanowire photocatalyst comprises the following steps: S1. adding a cesium source to octadecene, then adding oleic acid thereto, and then evacuating and heating, and then raising the temperature until the solid is completely dissolved to obtain a solution containing a cesium source; S2. The lead source is added to octadecene, and then oleylamine and octylamine ligands are added thereto, and then vacuum treatment is performed, and then the temperature is raised and kept warm for a certain period of time to obtain a solution containing a lead source; S3. A certain amount of a solution containing a cesium source is quickly added to a solution containing a lead source for reaction, and then the reaction is quenched; S4. Centrifuge the solution after the reaction, and centrifuge it again using a solvent in a subsequent centrifugation to obtain a stress-adjustable lead bromide cesium-based perovskite nanowire photocatalyst, which has a curved stress structure with adjustable curvature, and the curved stress structure is a curved ring structure.

[0006] Furthermore, the cesium source described in step S1 is cesium carbonate; the lead source described in step S2 includes one or more of lead chloride, lead bromide, and lead iodide.

[0007] Furthermore, the method for preparing the solution containing a cesium source described in step S1 comprises the following steps: adding 400 mg of a cesium source to 15 mL of octadecene, then adding 1.2 mL of oleic acid thereto, and then vacuuming and heating to 120°C, and after 1 h, raising the temperature to 150°C until the solid is completely dissolved, to obtain a solution containing a cesium source.

[0008] Furthermore, the method for preparing the lead source-containing solution described in step S2 comprises the following steps: adding 138 mg of the lead source to 16 mL of octadecene, then adding 2 mL of oleylamine and 0.4 mL of octylamine thereto, and then vacuuming the mixture, and after 1 hour, raising the temperature to 120°C and maintaining the temperature for 15 minutes to obtain a lead source-containing solution.

[0009] Furthermore, in step S3, the ratio of the cesium source to the lead source is 1:1-1:2.

[0010] Furthermore, step S3 specifically includes: taking 0.8 / 1.5 mL of the solution containing the cesium source and quickly adding it to the solution containing the lead source, reacting for 50 minutes, and then quenching the reaction in an ice water bath or at room temperature.

[0011] Furthermore, step S4 specifically includes: centrifuging the solution after the reaction at 7000 rpm for 10 min, using n-hexane as a solvent for subsequent centrifugation, and centrifuging again at 7000 rpm for 10 min, for a total of 3 washes.

[0012] The present invention also provides a stress-adjustable lead bromide cesium-based perovskite nanowire photocatalyst, wherein the main component of the photocatalyst is CsPbBr3, which contains a small amount of CsPb2Br5.

[0013] The present invention also provides an application of a stress-adjustable lead bromide cesium-based perovskite nanowire photocatalyst, which is applied in photocatalytic carbon dioxide reduction.

[0014] Compared with the existing technology, the breakthrough progress of the present invention is reflected in multiple dimensions. It not only profoundly innovates the design and synthesis strategy of photocatalysts, but also greatly promotes the photocatalytic carbon dioxide reduction technology towards a more efficient and controllable direction. Specifically, the technical advantages of the present invention and the significant progress it brings are specifically reflected in the following aspects: 1. The efficiency of photogenerated carrier separation is greatly improved.

[0015] When faced with the challenge of rapid recombination of photogenerated electron-hole pairs, traditional photocatalysts often find it difficult to effectively separate these carriers, thus limiting the further improvement of their photocatalytic activity. However, the present invention introduces a stress effect into CsPbBr3-based perovskite nanowires through carefully designed stress engineering. This innovative measure significantly improves the transmission path of photogenerated carriers and effectively inhibits their recombination process. Compared with one-dimensional CsPbBr3-based perovskite nanowire photocatalysts with unstressed structures, nanowires under stress regulation exhibit higher photogenerated carrier separation efficiency. This progress directly translates into faster reaction rates in the photocatalytic carbon dioxide reduction reaction, opening up new ways to achieve efficient and low-energy carbon dioxide conversion technology.

[0016] 2. Significant enhancement of photocatalytic performance.

[0017] The core of photocatalytic carbon dioxide reduction technology is how to efficiently and stably convert greenhouse gas carbon dioxide into valuable chemicals or fuels. The CsPbBr3-based perovskite nanowire photocatalyst of the present invention, under the action of stress regulation, not only improves the light absorption efficiency and the separation efficiency of photogenerated carriers, but also optimizes the reaction active sites on the catalyst surface, so that its adsorption and activation ability for carbon dioxide molecules is significantly enhanced. This series of chain reactions directly leads to a significant improvement in the performance of photocatalytic carbon dioxide reduction, including but not limited to higher product selectivity, faster reaction kinetics and longer catalyst service life, laying a solid foundation for the realization of industrial applications.

[0018] 3. Innovation and simplification of preparation methods.

[0019] The preparation of traditional perovskite-based catalysts often involves complex process flows and harsh reaction conditions, which not only increases production costs but also limits the large-scale production of catalysts. The present invention achieves precise regulation of the stress of one-dimensional perovskite nanowires through a simple and easy-to-control reaction condition adjustment strategy. This innovative preparation method not only simplifies the preparation process and reduces production costs, but also provides researchers with a new idea, that is, to regulate the physical and chemical properties of the catalyst through stress engineering, thereby optimizing its catalytic performance. This flexible and changeable preparation method provides valuable guidance and reference for the development of more high-performance perovskite-based catalysts.

[0020] In summary, the CsPbBr3-based perovskite nanowire photocatalyst of the present invention exhibits significant technical advantages in terms of photogenerated carrier separation efficiency, photocatalytic performance and preparation method. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 HRTEM images (HRTEM is the abbreviation of high resolution transmission electron microscope) of the CsPbBr3-based perovskite nanowire photocatalyst with different stress sizes synthesized in the embodiments of the present invention and the CsPbBr3 perovskite nanowire photocatalyst synthesized in the embodiments when the cesium source is added in an amount of 0.8 mL and quenched in an ice-water bath, the cesium source is added in an amount of 0.8 mL and quenched at room temperature, and the cesium source is added in an amount of 1.5 mL and quenched in an ice-water bath.

[0022] Figure 2 It is the XRD diagram of CsPbBr3-based perovskite nanowire photocatalyst with different stress sizes synthesized in the embodiment of the present invention (XRD is the abbreviation of X-ray diffraction).

[0023] Figure 3 It is a Raman graph (Raman is the abbreviation of Raman spectra, i.e. Raman spectrum) of CsPbBr3-based perovskite nanowire photocatalysts with different stress sizes synthesized in an embodiment of the present invention.

[0024] Figure 4 This is a comparison chart of the activity of CsPbBr3-based perovskite nanowire photocatalysts with different stress sizes synthesized in an embodiment of the present invention for reducing carbon dioxide.

[0025] Figure 5 PL images (PL is the abbreviation of Photoluminescence, i.e., fluorescence spectrum) of CsPbBr3-based perovskite nanowire photocatalysts with different stress sizes synthesized in an embodiment of the present invention.

[0026] Figure 6 This is the UV-Vis graph of CsPbBr3-based perovskite nanowire photocatalysts with different stress sizes (UV-Vis is UV-Visible adsorption spectra). DETAILED DESCRIPTION

[0027] The following is a detailed description in conjunction with the embodiments of the present invention.

[0028] Example 1 A method for preparing a zero-dimensional CsPbBr3 perovskite quantum dot photocatalyst comprises the following steps: 400 mg Cs2CO3 was added to 15 mL octadecene, followed by 1.2 mL oleic acid, vacuum treatment and heating to 120 ° C. After 1 h, the temperature was raised to 150 ° C until the solid was completely dissolved to obtain a solution containing a cesium source. 138 mg PbBr2 was added to 16 mL octadecene, followed by 2 mL oleylamine and 0.4 mL octylamine, vacuum treatment, and then the temperature was raised to 120 ° C after 1 h. After 15 min, 0.8 / 1.5 mL of the cesium source solution was quickly added to the lead source solution. After 50 min of reaction, the reaction was quenched in an ice water bath or at room temperature. Finally, the reacted solution was centrifuged at 7000 rpm for 10 min, and n-hexane was used as the solvent for subsequent centrifugation. It was centrifuged again at 7000 rpm for 10 min, and washed 3 times in total.

[0029] The CsPbBr3-based perovskite nanocatalyst synthesized in Example 1 was tested by TEM. Figure 1 As shown, when the amount of cesium source solution added is 0.8 mL and the reaction is quenched in an ice-water bath, the obtained nanowires have a highly curved ring structure; when the amount of cesium source solution added is 0.8 mL and the reaction is quenched at room temperature, the obtained nanowires have an unclosed structure with a certain curvature; when the amount of cesium source solution added is 1.5 mL and the reaction is quenched in an ice-water bath, the obtained nanowires are close to a straight line structure.

[0030] The CsPbBr3-based perovskite nanowire catalyst synthesized in Example 1 was subjected to XRD test, and the results were as follows: Figure 2 As shown, it shows that the main component of all catalysts is CsPbBr3, among which the nanowires with bent structures contain a small amount of CsPb2Br5 and can correspond to the standard card.

[0031] The CsPbBr3-based perovskite nanowire catalyst synthesized in Example 1 was subjected to Raman testing, and the results were as follows: Figure 3 As shown, the change in the displacement direction of the corresponding characteristic peak also shows that the stress magnitude of the catalyst is consistent with the degree of bending.

[0032] The above results illustrate the successful preparation of CsPbBr3-based perovskite nanocatalysts with tunable stress.

[0033] The photocatalytic reduction of carbon dioxide performance of the above catalyst was evaluated, and the specific steps were as follows: the CsPbBr3 photocatalyst dispersion prepared in Example 1 was evenly drop-coated on a glass fiber membrane with a diameter of 4 cm, and dried in a vacuum oven at 60°C for 24 h. The membrane was then placed in a Magnesium CO2 reduction system (MC-SPB10) equipped with a 300 W xenon lamp, and the system was repeatedly vacuumed and injected with CO2 three times, and then 0.1 mL of pure water was injected, and the light source was turned on. During the test, the product was automatically detected by a gas chromatograph (GC) connected to the equipment.

[0034] Figure 4 This is a comparison chart of the photocatalytic reduction of carbon dioxide activity of the CsPbBr3-based perovskite nanowire catalysts synthesized in Example 1. It can be seen that all catalysts selectively reduce CO2 to CO, among which the nanowire catalyst with moderate stress has the highest performance of 150.2 μmol -1 g -1 h -1 , respectively, the nanowire catalyst with the highest stress (88.1 μmol -1 g -1 h -1 ) and 5 times that of the unstressed nanowire catalyst (27.7 μmol -1 g -1 h -1 ).

[0035] In order to explore the reasons why stress affects the performance of CsPbBr3 nanowire photocatalysts, UV and PL tests were performed on the catalyst prepared in Example 1. Figure 5 As shown in Figure 2, the light absorption performance of CsPbBr3-based nanowires with stress structures is lower than that of CsPbBr3-based nanowires without stress, indicating that the performance improvement has nothing to do with the light absorption properties. Figure 6 As shown, the fluorescence intensity of CsPbBr3-based nanowires with moderate stress is the lowest, which indicates that the photogenerated carrier separation efficiency in the one-dimensional nanowire structure with moderate stress is the highest.

[0036] The present invention prepares a stress-adjustable CsPbBr3-based perovskite nanowire photocatalyst and applies it to photocatalytic reduction of carbon dioxide. The performance of the CsPbBr3-based perovskite nanowire photocatalyst with moderate stress is 5 times that of the stress-free CsPbBr3-based perovskite nanowire photocatalyst; the stress structure improves the separation efficiency of photogenerated carriers.

[0037] Finally, it should be noted that through the embodiments described in the patent of the present invention, ordinary technicians in this field can make similar changes and adjustments under the enlightenment of the present invention without violating the spirit and claims of the present invention, and such changes fall within the scope of protection of the present invention.

Claims

1. A method for preparing a stress-adjustable lead bromide cesium-based perovskite nanowire photocatalyst, characterized in that: The following steps are involved: S1. adding a cesium source to octadecene, then adding oleic acid thereto, and then evacuating and heating, and then raising the temperature until the solid is completely dissolved to obtain a solution containing a cesium source; S2. The lead source is added to octadecene, and then oleylamine and octylamine ligands are added thereto, and then vacuum treatment is performed, and then the temperature is raised and kept warm for a certain period of time to obtain a solution containing a lead source; S3. Controlling the amount of the solution containing the cesium source to react with the solution containing the lead source, and then controlling the conditions to quench the reaction; S4. Centrifuge the solution after the reaction, and centrifuge it again using a solvent in a subsequent centrifugation to obtain a stress-adjustable lead bromide cesium-based perovskite nanowire photocatalyst, which has a curved stress structure with adjustable curvature, and the curved stress structure is a curved ring structure.

2. The method for preparing the stress-adjustable lead bromide cesium-based perovskite nanowire photocatalyst according to claim 1, characterized in that: The cesium source described in step S1 is cesium carbonate; the lead source described in step S2 includes one or more of lead chloride, lead bromide, and lead iodide.

3. The method for preparing the stress-adjustable lead bromide cesium-based perovskite nanowire photocatalyst according to claim 1, characterized in that: The method for preparing the solution containing a cesium source described in step S1 comprises the following steps: adding 400 mg of a cesium source to 15 mL of octadecene, then adding 1.2 mL of oleic acid thereto, and then vacuuming and heating to 120° C., and after 1 h, raising the temperature to 150° C. until the solid is completely dissolved, thereby obtaining a solution containing a cesium source.

4. The method for preparing the stress-adjustable lead bromide cesium-based perovskite nanowire photocatalyst according to claim 1, characterized in that: The method for preparing the lead source-containing solution described in step S2 comprises the following steps: adding 138 mg of the lead source to 16 mL of octadecene, then adding 2 mL of oleylamine and 0.4 mL of octylamine thereto, and then vacuuming the mixture. After 1 hour, the temperature is raised to 120° C. and maintained for 15 minutes to obtain a lead source-containing solution.

5. The method for preparing the stress-adjustable lead bromide cesium-based perovskite nanowire photocatalyst according to claim 1, characterized in that: In step S3, the ratio of the cesium source to the lead source is 1:1-1:

2.

6. The method for preparing the stress-adjustable lead bromide cesium-based perovskite nanowire photocatalyst according to claim 1, characterized in that: Step S3 specifically includes: taking 0.8 / 1.5 mL of the solution containing the cesium source and quickly adding it to the solution containing the lead source, reacting for 50 minutes, and then quenching the reaction in an ice water bath or at room temperature.

7. The method for preparing the stress-adjustable lead bromide cesium-based perovskite nanowire photocatalyst according to claim 1, characterized in that: Step S4 specifically includes: centrifuging the solution after the reaction at 7000 rpm for 10 min, using n-hexane as a solvent for subsequent centrifugation, and centrifuging again at 7000 rpm for 10 min, for a total of 3 washes.

8. A stress-adjustable lead bromide cesium-based perovskite nanowire photocatalyst prepared according to the method of any one of claims 1 to 7.

9. The stress-adjustable lead bromide cesium-based perovskite nanowire photocatalyst according to claim 8, characterized in that: The main component of the photocatalyst is CsPbBr3, which contains a small amount of CsPb2Br5.

10. An application of the stress-adjustable lead bromide cesium-based perovskite nanowire photocatalyst according to claim 8 or 9, characterized in that: Applied in photocatalytic carbon dioxide reduction.

Citation Information

Patent Citations

  • Stress-controlled catalyst film electrode and preparation method and application thereof

    CN108950481A

  • Preparation method and application of perovskite type LaCoO3 visible light conductive film

    CN116730399A

  • Preparation method and application of photocatalytic material with controllable internal stress and unsaturation degree

    CN117299140A

  • One-dimensional cesium lead bromide perovskite nanowire photocatalyst, preparation method and application of one-dimensional cesium lead bromide perovskite nanowire photocatalyst in reduction of carbon dioxide

    CN117463379A

  • Stress-induced light emitting materail-photocatalyst composite

    JP2009142771A